Footwear Design Considerations for an Aging Population from User Experience, Service, and Technology Aspects. (September 2022) - Lee, Sheng-Hung; Lee, Chaiwoo; Yang, Maria C.; Coughlin, Joseph F.
Growth of the aging population is a systemic, social-technological challenge facing the world. Typical ways of designing and developing products for older adults have been disrupted by this demographic shift and the introduction of new technologies. This study focuses on indoor footwear design for an aging population to help designers consider aspects of user experience, service, and technology. We investigated older adults' use and purchasing behavior through surveys and semi-structured interviews. We presented ten smart footwear concepts and ideas around internet-of-things (IoT) wearable devices, data privacy, and security issues to help identify their unmet desires and pain points. We conclude that, for older adults, wearing shoes represents their independence in life, that their foot healthcare problems vary widely, and that they are not equipped with the proper/optimal knowledge to choose the right footwear. Designers need to consider their physical limitations and cognitive load while conducting such research.